Pengaruh Harga, Lokasi Dan Citra Merek Terhadap Keputusan Pembelian Produk Merek Mixue Di Kota Medan - Hutasoit, Wita Gusti Purnama; Sianturi, Charles M.; Sihombing, Natalia E. (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
The purpose of this study was to measure the effect of price, location and brand image on purchasing decisions for Mixue products in Medan city. This study uses quantitative methods with nonprobability sampling techniques and purposive sampling approaches with a sample size of 100 respondents, The data collection technique was carried out by distributing questionnaires to Mixue consumers with purchases in the last 12 months. the data was analyzed using multiple regression analysis which begins with validity, reliability, classical assumptions, coefficient of determination, F test and t test conducted using SPSS Statistics version 25. Based on the partial t test and simultaneous F test, it shows that the three independent variables have a positive and significant effect on purchasing decisions for Mixue products. Based on the coefficient of determination R2, it is known that the three independent variables explain 0.618%, the variability of Mixue product purchase data and the rest is explained by other variables not examined in this study.